2007
DOI: 10.1021/ic7014176
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Steric Hindrance on the Core Geometry and Sulfoxidation Chemistry of Carboxylate-Rich Diiron(II) Complexes

Abstract: The asymmetric terphenyl-2'-carboxylate ligand 3,5-dimethyl-1,1':3',1' '-terphenyl-2'-carboxylate, -O2CArPh,Xyl, was prepared in high yield. This ligand facilitates the assembly of the diiron(II) complexes [Fe2(micro-O2CArTol)2(O2CArPh,Xyl)2(THF)2] [2, -O2CArTol=2,6-di-p-tolylbenzoate], [Fe2(micro-O2CArTol)2(O2CArPh,Xyl)2(pyridine)2] (5), [Fe2(micro-O2CArPh,Xyl)2-(O2CArPh,Xyl)2(THF)2] (3), and [Fe2(micro-O2CArPh,Xyl)2(O2CArPh,Xyl)2(pyridine)2] (6), all of which have a windmill geometry. The iron-iron distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Certainly, an understanding of the molecular determinants of BMM substrate specificity, regioselectivity and enantioselectivity properties is preliminary to the rational design of new, improved catalysts, as proved by the large number of studies on BMM catalytic mechanisms and on synthetic analogues capable of catalyzing reactions similar to those catalyzed by BMMs (14,28,39).…”
mentioning
confidence: 99%
“…Certainly, an understanding of the molecular determinants of BMM substrate specificity, regioselectivity and enantioselectivity properties is preliminary to the rational design of new, improved catalysts, as proved by the large number of studies on BMM catalytic mechanisms and on synthetic analogues capable of catalyzing reactions similar to those catalyzed by BMMs (14,28,39).…”
mentioning
confidence: 99%
“…The Fe–S distance in the thioether complex is 3.090 Å, which indicates a very weak interaction between the two atoms made possible by the larger size and more diffuse orbitals of sulfur. [25] In the case of the phenoxypyridine complex, however, no bonding interaction is feasible at an Fe–O distance larger than 3 Å and the complex therefore adopts the typical windmill structure. It is unlikely that the use of different carboxylates, – O 2 CAr Tol vs. – O 2 CAr 4-FPh , would affect the coordination geometry.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike previous diiron compounds with tethered substrates, the phenyl ring is located farther from the diiron center, as found by X-ray crystallographic structural analysis, and might be sterically unable to approach the oxygenated diiron center. [22-25,29] The oxidation of tethered phosphine and sulfide groups in analogous diiron systems revealed that the extent of oxidation diminishes when the substrate is systematically moved away from the diiron center. [23-25] In order to test this hypothesis, the tethered substrates would need to be redesigned to bring them closer to the diiron center.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fortuitous discovery that high-valent diiron terphenylcarboxylate complexes could be intercepted by tethered substrates inspired subsequent studies of the reactivity of oxygenated intermediates toward organic moieties held in close proximity to the diiron center. Attachment of benzyl [84, 85], ethyl [85], ethynyl [86], phenoxyl [87], phosphido [84, 88], or sulfido [88, 89] units to an amine or pyridine ligand afforded a series of tethered substrates that could be easily incorporated into 13 , affording the corresponding diiron(II) compounds. After exposing the substrate/diiron(II) complex to O 2 , the reaction products were analyzed by gas chromatography-mass spectrometry (GC-MS).…”
Section: Ligand Platformsmentioning
confidence: 99%